Remarkably Low Oxygen Evolution Reaction Overpotentials using Two-Dimensional Ternary Vanadium Compounds - Sial, Qadeer Akbar; Ali, Rana Basit; Waqas, Muhammad; Lee, Young Jae; Kalanur, Shankara S.; Seo, Hyungtak (Applied Surface Science, 2023)
Lowering the overpotentials to drive the oxygen evolution reaction (OER) during the water-splitting process is the bottleneck process and holds the key to achieving cost-effective and efficient electrolysis infrastructure systems. Given this, here we report the first demonstration of utilizing a catalyst derived from lead vanadate (PVO) for alkaline electrolysis systems with record low overpotentials. The synthesis route was regulated to yield a two-dimensional (2-D) PVO structure with uniform coatings on the Ni electrode. The optimized PVO demonstrated impressively low overpotentials of 146 mV vs RHE for OER at a current density of 10 mAcm−2. The excellent OER performance was attributed to the 3D structures assembled from porous 2D PVO that promotes a facile ionic transport and accelerates electron transfer in OER electrochemical process. Importantly, the proposed approach will open a new window for possible exploitation and practical utilization of ternary vanadium oxides in alkaline electrolysis in the future.
Keywords: 2D structures; Alkaline electrolysis; Bottleneck process; Cost effective; Lead vanadate; Low oxygen; Overpotential; Splitting process; Two-dimensional; Water splitting; 2D structure; Electrolysis; Lead vanadate; Overpotential; Oxygen evolution reaction